Ecological Tendencies in Shaykh Nawawi al-Bantani’s Tafsir Maraḥ Labid : A Study of Environment-Related Qur'anic Verses - Makfi, Muhammad Miqdam (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2026)
Generation Z students in Islamic boarding schools (pesantren) increasingly face complex mental challenges such as anxiety, emotional instability, and a sense of meaninglessness. These issues are intensified by academic pressures, digital culture, and identity transitions. Addressing such problems requires a Qur’anic framework that provides both spiritual guidance and practical solutions. This study aims to explore the Qur’anic concept of Tazkiyat al-Nafs as a spiritual strategy to overcome mental challenges among Generation Z in pesantren, and to evaluate its relevance in fostering resilience, self-discipline, and stable spirituality. Employing Abdul Hayy al-Farmawi’s thematic exegesis (Tafsir Maudhu’i), this research adopts a qualitative case study design at Ma’had Daarul Qur’an Langsa. Data were collected through textual analysis of Qur’anic verses related to purification, struggle (mujahadah), patience, gratitude, sincerity, and piety, complemented by in-depth interviews and direct observation of students and teachers. Data analysis involved reduction, categorization, and thematic interpretation. Findings reveal that Qur’anic principles effectively address Gen-Z mental challenges. Tazkiyat al-Nafs purifies the soul from negative traits; Mujahadah cultivates discipline; patience and gratitude strengthen resilience; while sincerity and piety establish stable spirituality. These practices reduce anxiety, enhance emotional regulation, and restore meaning in students’ lives. The Qur’anic concept of Tazkiyat al-Nafs is relevant and applicable to the mental challenges of Generation Z in pesantren. Integrating thematic exegesis into pesantren education is recommended as a holistic approach to reinforce students’ mental and spiritual well-being. Krisis ekologis merupakan problem yang telah muncul sejak abad ke 19. Berbagai respon muncul dari berbagai kalangan dan golongan. Respon dari umat Islam tentunya juga mutlak diharapkan agar Islam benar-benar menjadi agama yang relevan, kapanpun, di manapun. Relevansi Islam yang tak lekang oleh tempat dan waktu ini harusnya terejewantahkan secara prinsipil pada penafsiran ayat-ayat Al-Quran. Marah Labid karya Syaikh Nawawi al-Bantani, sebagai karya tafsir yang muncul di abad 19-an Masehi, ketika revolusi industri masih hangat dan memunculkan banyak problem lingkungan, seyogyanya turut andil merespon masalah ekologis tersebut. Menggunakan teori hifẓ al-bī‘ah (menjaga lingkungan) dalam Maqashid al-Syariah, peneliti berusaha menelisik penafsiran Syaikh Nawawi terhadap ayat-ayat Al-Quran yang berkaitan dengan kelestarian lingkungan. Dengan analisis deskriptif, penelitian pustaka ini menggunakan Tafsir Marah Labid karya Syaikh Nawawi sebagai sumber sekunder utama ditambah berbagai sumber-sumber tambahan lain. Hasil penelitian menunjukkan bahwa Syaikh Nawawi, dalam tafsirnya Marah Labid, secara spesifik belum menunjukkan kecenderungan praktis maupun teoretis terhadap kelestarian lingkungan yang sebenarnya sudah bermasalah sejak di masa Syaikh Nawawi sendiri. Terma fasad (kerusakan) di muka bumi selalu disebut sebagai azab Allah akibat dosa dan maksiat manusia, bukan pada aktivitas perusakan lingkungan yang sering dilakukan manusia. Penelitian ini diharapkan dapat memperluas pengetahuan akademisi terkait respon ulama tafsir terhadap isu-isu kontemporer.